Electrical behaviour and microstructural characterization of magnesia co-doped ScSZ nanopowders synthesized by urea co-precipitation - Accardo, G.; Dell'agli, G.; Frattini, D.; Spiridigliozzi, L.; Nam, S.W.; Yoon, S.P. (Italian Association of Chemical Engineering - AIDIC, 2017)
In this study Scandia-doped zirconia co-doped with MgO, (MgO)0.03(ZrO2)0.88(Sc2O3)0.09, was synthetized by using the urea co-precipitation method in hot aqueous solution. MgO was added to prevent the transformation of cubic fluorite Sc-doped ZrO2 into rhombohedral phase, with worst electrical properties. The as-prepared powders were completely amorphous and, by a calcination step at 500 °C for 1 h, full conversion to fluorite phase occurred preserving the nano size character of powders. The presence of MgO allowed to effectively stabilize the cubic fluorite phase also after a prolonged thermal treatment at 1200 °C. The nanometric feature of the powder aided the sintering step of this material at 1600 °C. The EIS electrical characterization revealed that its ionic conductivity is 7.3.10-2 S/cm and 2.8.10-2 S/cm at 800 °C and 700 °C, respectively. Therefore, this material is suitable as ceramic electrolyte in SOFC operated at intermediate temperatures. ？ Copyright 2017, AIDIC Servizi S.r.l.